Effect of soaking on Gaharu essential oil yield using microwave assisted extraction: article - Baharuddin, Muhamad Ikhwan; Che Radzi, Nurhaslina (2018)
The extraction of oil can be done using hydrodistillation, steam distillation and supercritical fluid extraction (SFE). However, for this experiment hydrodistillation method is chosen because it is the simplest method but required long time to extract the oil. The objective of this study is to identify the effect of soaking towards the essential oil yield using microwave assisted extraction. The essential oil then will be analyse using gas chromatographymass spectrometer (GC-MS). The gaharu will be soaked with distilled water at 2,5 and 7 days and will be extracted using MAE. The power of the microwave is constant at 540 W and the temperature is 94.50C. The time taken for the experiment to run is 12 hours. A total of 3 major compounds which are benzaldehyde, cyclopentane acetic acid and ethanone were identified from the four sample of gaharu residue. The soaking process for 7 days shows the highest amount of component compared to other soaking for 2 and 5 days. This result shows, the cell has expanded and finally damage, thus releasing the content of the soaking water